Effects of vapocoolant spray on skin sterility prior to intravenous cannulation. Issue 4 (August 2015) - Evans, J.G.; Taylor, D. McD.; Hurren, F.; Ward, P.; Yeoh, M.; Howden, B.P.
Summary Background Alkane vapocoolant sprays evaporate rapidly, lower skin temperature and result in a temporary interruption in pain sensation. They reduce the pain of intravenous cannulation. However, concern exists that they may recontaminate the sterile cannulation site. Aim To determine the effects of vapocoolant spray on skin sterility prior to cannulation. Methods Fifty patients from the emergency department of a large tertiary metropolitan hospital were enrolled in this study. Bacterial skin swabs were taken from the dorsum of both hands of each patient. From one hand, a swab was taken following standard chlorhexidine disinfection, and a second swab was taken following the application of vapocoolant spray. From the other hand, a swab was taken from unprepared (non-disinfected) skin, and a second swab was taken following vapocoolant application. Skin swabs were sent for microbiological culture and quantitative comparison. Findings The administration of vapocoolant after skin disinfection did not increase the bacterial colony count significantly: median 0.0 [interquartile range (IQR) 0.0] vs 0.0 (IQR 0.0) (P = 0.71). The administration of vapocoolant to the unprepared skin decreased the colony count significantly: median 33.5 (IQR 68) vs 3.0 (IQR 11) (P < 0.001). Conclusion Alkane vapocoolant spray does not recontaminate the skin after disinfection, and should pose no increased risk of infection when used as an anaesthetic agent prior to intravenous cannulation following disinfection. While it does have inherent bactericidal activity, this is not sufficient for it to be used as the sole disinfectant.